Cross-Cultural Management of COVID-19 Pandemic: Array - Genc, Ruhet; Dede, Merve Ahter (Acta Universitatis Danubius. Œconomica, 2020)
As the novel coronavirus disease 2019 (COVID-19) spread throughout the world and proclaimed a pandemic, governments around the world have implemented countless unparalleled policies in response to the pandemic. Preventative techniques such as close management of infection, patient isolation, and social distancing. However, in the absence of a particular antiviral or vaccine recommended for the treatment of COVID-19, pandemic control often includes minimizing virus transmission by effective policy interventions. Although most of these steps are successful, they bring economic and social burden. The goal of this paper is to analyze, from a cross-cultural viewpoint, the management of the COVID-19 pandemic. The paper comprehensively synthesizes the evidence on conditions during this emergency and suggests several measures to control and mitigate the risks relating to it, taking into account the most recent data presented by agencies such as WHO and CDC. This paper's approach will be a literature review and a critical examination of the results. This analysis might be used by policymakers and health authorities for responding to the global challenges posed by the pandemic, such as strain on health care structure, resource allocation, and supply chain disruptions, for decelerating its propagation, and for planning before similar situations in the future